The rolle of carbohydrate component of neutrophil membrane glycoprotein receptors for change of its functional activity at patients with acute coronari syndroms and its combination with diabetes mellitus type 2 - V. F. Kiritchuk; N. A. Koscheleva; A. P. Rebrov (Бюллетень сибирской медицины)
The aim of this work is to gind ont influence of сarbohydrate сomponent of membrane glycoprotein receptors on the change of its functional activity at patients with acute coronari syndromes and its combination with diabetes mellitus type 2. 69 sich men and 20 nearly healthy men were examined. Among the patients 32 men sugger from acute coronari syndromes, 17 men — from combination with diabetes mellitus type 2 and 20 men — from diabetes mellitus type 2 only. Neutrophil aggregation induced by method by Gabbasov and another autors (1989). Wheat Germ Agglutinin (WGA), Concanavalin A (Con A), Phitogemagglutinin (PHA). At patients with acute coronari syndromes aggregation of neutrophile isincreaced under affect of N-acetyl-D-glucosamin and acidi syalici and at patients with diabetes mellitus type 2 — under affect of mannose and bD-galactose. In the case of the combination of acute coronari syndromes and diabetes mellitus type 2 the rise of aggregation is connected not only with increase of mannose and bD-galactose but also with increase of N-acetyl-D-glucosamin and acidi syalici. Neutrophile' carbohydrate structure is restored under affect of defenite therapy.